Determinants of first birth interval in an Indian scenario: National Family Health Survey based analysis - Patil, Anushri P.; Tyagi, Naresh Kumar; Shitole, Abhijeet B.; Prasad, Jang Bahadur (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: First birth interval (FBI), a time gap between marriage and first live birth is an important predictor of population size of a country and has a significant impact on its age structure. Longer FBI (delayed fertility) is a burning issue in modern India and has socioeconomic, demographic, and biological determinants. It represents reproductive behaviour and capabilities of Indian couples. The determinants of prolonged FBI have not been analysed in Indian scenario yet. We aimed at evaluating first birth interval at 84 months and above to highlight the factors responsible for delayed fertility and produce evidence that can modify or improve the current reproductive health program policies in India. Methods: Statistical analysis of sociodemographic data obtained from the National Family Health Survey-4 (NFHS-4, 2015-16) of Indian women in their reproductive age (15-49 years) and married for 7 years and above and having either a child delivered or yet to deliver it after 84 months of marriage was done to draw meaningful conclusions. Results: 24% women had FBI of 84 months and above. Age at marriage had an “U-shaped” association with delayed fertility, early and late marriages exhibiting higher risk for delayed childbearing. Education of women was the most important determinant of prolonged FBI followed by wealth index, body mass index, religion, and residence. Conclusions: This insight in Indian fertility dynamics highlights need of reformulating the reproductive health policies for better program outcomes in India.